Autoeficacia percibida de las competencias profesionales en psicólogos clínicos - Buele Unuzungo, Keily Del Cisne; Orellana Zambrano, Karen Lisbeth (My University, 2025)
Self-efficacy, understood as the belief in one's own ability to successfully carry out specific tasks, is a key factor in professional adjustment, particularly during the initial stages of clinical practice. This study approached self-efficacy from a cognitive-behavioral perspective, grounded in the theories of Aaron Beck and Albert Ellis, which emphasize the interaction between thoughts, emotions, and behaviors in shaping professional judgment, decision-making, and clinical confidence. The objective of this research was to understand the perceived self-efficacy of professional competencies among recently graduated clinical psychologists from the Technical University of Machala, exploring how they construct perceptions of their performance in essential functions such as assessment, intervention, and ethical decision-making. A qualitative-descriptive methodology with a phenomenological approach was used, allowing for an in-depth exploration of participants' experiences within their natural clinical work contexts. Data collection techniques included semi-structured interviews and non-participant observation. The sample consisted of four female psychologists who had graduated approximately one year prior, selected through purposive non-probability sampling. The results showed that professional self-efficacy is a dynamic phenomenon shaped by factors such as feedback, supervision, exposure to real cases, and the level of clinical self-reflection. Participants demonstrated a growing sense of competence, particularly in assessment and intervention, although they also expressed insecurities when facing highly complex emotional or technical situations. It is concluded that perceived self-efficacy develops progressively and is closely linked to professional support, supervised training, and reflective spaces on practice. This study offers a contextualized perspective on the strengths and needs of early-career clinical psychologists, emphasizing the importance of strengthening support networks, ethical supervision processes, and ongoing training in practical competencies.
La autoeficacia, entendida como la creencia en la propia capacidad para ejecutar con éxito determinadas tareas, constituye un factor determinante en el ajuste profesional, especialmente durante las etapas iniciales del ejercicio clínico. En este estudio, se abordó dicha construcción desde el enfoque cognitivo-conductual, sustentado en las teorías de Aaron Beck y Albert Ellis, que reconocen la interacción entre pensamientos, emociones y conductas en la configuración del juicio profesional, la toma de decisiones y la seguridad clínica. El objetivo de la investigación fue comprender la autoeficacia percibida de las competencias profesionales en psicólogos clínicos recientemente graduados de la Universidad Técnica de Machala, explorando cómo construyen la percepción de su desempeño en funciones esenciales como la evaluación, la intervención y el manejo ético. Se empleó una metodología cualitativa-descriptiva, con enfoque fenomenológico, que permitió explorar en profundidad las vivencias de las participantes en su contexto natural de trabajo clínico. Las técnicas de recolección incluyeron entrevistas semiestructuradas y observación no participante. La muestra estuvo conformada por cuatro psicólogas graduadas hace aproximadamente un año, seleccionadas mediante muestreo no probabilístico a conveniencia. Los resultados mostraron que la autoeficacia profesional es un fenómeno dinámico, moldeado por factores como la retroalimentación, la supervisión, el contacto con casos reales y el nivel de autorreflexión clínica. Las participantes evidenciaron un sentido creciente de competencia, particularmente en evaluación e intervención, aunque también expresaron inseguridades ante situaciones de alta complejidad emocional o técnica. Se concluye que la autoeficacia percibida se construye de forma progresiva y está estrechamente vinculada al acompañamiento profesional, la formación supervisada y los espacios de reflexión sobre la práctica. Este estudio ofrece una mirada contextualizada sobre las fortalezas y necesidades de las psicólogas clínicas en etapa inicial, subrayando la importancia de fortalecer las redes de apoyo, los procesos de supervisión ética y la formación continua en competencias prácticas.
Keywords: AUTOEFICACIA PROFESIONAL; PSICOLOGÍA CLÍNICA; EVALUACIÓN PSICOLÓGICA; COMPETENCIAS